Method for measuring contents of multiple components in stuffing sand components

By combining melt sample preparation and X-ray fluorescence method melting sheet analysis, the problem of complex, high cost and poor accuracy of zirconium drainage sand component content measurement methods in the prior art is solved, and efficient and accurate multi-component content measurement is achieved.

CN119438273APending Publication Date: 2025-02-14CHENGDE JIANLONG SPECIAL STEEL
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411615416.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing zirconium drainage sand component content measurement methods have problems such as cumbersome operation, high cost, easy volatility of chromium elements, and the use of organic toxic reagents, and it is impossible to accurately determine the content of multiple elements at the same time.

Method used

The composition analysis of drainage sand can be analyzed by combining melt sample preparation and X-ray fluorescence method, so that chromium trioxide, silica, iron trioxide, aluminum trioxide and zirconium dioxide can be measured at one time. etc.

Benefits of technology

It improves detection efficiency, high accuracy, and does not involve improving the particle effect problem in tableting analysis, reducing operational complexity and cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119438273A_ABST
    Figure CN119438273A_ABST
Patent Text Reader

Abstract

The invention provides a method for determining the content of multiple components in stuffing sand, which comprises the following steps of: performing component analysis on the stuffing sand by adopting a mode of combining melting sample preparation and X-ray fluorescence method fuse piece analysis, fitting a standard sample piece correction working curve, performing repeatability and reproducibility tests, determining the applicability of the method, and determining the content of multiple components in the stuffing sand. And performing component analysis on the to-be-detected stuffing sand sample wafer by using an X-ray fluorescence method to obtain the stuffing sand sample wafer. According to the present invention, the component analysis is performed on the stuffing sand by combining the melting sample preparation and the X-ray fluorescence method fuse piece analysis, such that the contents of chromium sesquioxide, silicon dioxide, iron sesquioxide, aluminum oxide, zirconium dioxide and other substances in the stuffing sand can be obtained at the one time, and the determination method improves the detection efficiency, and has characteristics of high sensitivity and high accuracy. Fuse piece analysis does not relate to improvement of the particle effect problem in tabletting analysis, and the accuracy is high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of chemical substance analysis method detection, and particularly relates to a method for determining the content of multiple components in drainage sand. Background Art

[0002] Drainage sand is made of forsterite from Henan and fused magnesia from Dashiqiao, Liaoning as the main raw materials, and carbon materials from Yichang, Hubei as additives, and is combined according to specific particle sizes and weight percentages, and mixed to prepare drainage sand. After trial use, it has been proved that the drainage sand has good dispersion and fluidity, high refractoriness, no sintering, no clogging, and a steel tapping rate and drainage rate of 100%. The use temperature is ≥1750℃, and it does not chemically react with molten steel and alloy components. The storage quality does not change. It can meet the requirements of steelmaking process. It is the most ideal refractory material for eccentric furnace steelmaking and a ladle bottom material.

[0003] There are four basic conditions for drainage sand used in ladle drainage: the drainage sand is kept at high temperature for a long time at the ladle nozzle, requiring the sintering layer to have high refractoriness; the drainage sand is directly in contact with the molten steel after filling the nozzle, and the initial sintering temperature is not easy to be too high; during use, the drainage sand is subjected to a large static pressure of the molten steel, and in order to prevent the material from being stretched, the drainage sand is required to have very good fluidity and the friction between the particles is as small as possible; the drainage sand is kept at high temperature to prevent the drainage sand from automatically falling or failing to effectively support the upper material during use. Based on the above requirements, there are four common types of drainage sand that meet the actual application: forsterite, silica, zirconium and chromium drainage sand.

[0004] The difference in the content of drainage sand components directly affects the quality of the sample. At present, the method for determining the content of each component of zirconium drainage sand is mainly based on chemical analysis, which has the following shortcomings: Due to the special composition structure of zirconium drainage sand, a large amount of acid and alkali reagents are required for dissolution, which makes the operation cumbersome and the cost high: During the dissolution process of the sample, the chromium element is easy to volatilize and difficult to accurately determine: When determining the content of ZrO2 in the sample, the organic toxic reagent phenylacetic acid is required, which poses a risk of endangering personal safety and polluting the environment; it is impossible to determine the content of multiple elements at the same time, so the analysis cycle is long. Since there are great technical difficulties in the determination of the content of each component in zirconium drainage sand, it is difficult to meet the needs of workshop material testing, so there is an urgent need to find an efficient, fast, low-cost and less polluting alternative method.

[0005] Therefore, it is of great significance to develop a method for determining the content of multiple components in drainage sand with high accuracy and simple operation. Summary of the invention

[0006] The object of the present invention is to provide a method for determining the content of multiple components in drainage sand. The method adopts a combination of fusion sample preparation and X-ray fluorescence melt analysis to perform component analysis on the drainage sand, and can obtain the contents of substances such as chromium trioxide, silicon dioxide, iron trioxide, aluminum trioxide and zirconium dioxide in the drainage sand at one time. The method improves the detection efficiency, and the melt analysis does not involve the problem of improving the particle effect in the pressed tablet analysis, and has a high accuracy.

[0007] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0008] The present invention provides a method for determining the content of multiple components in drainage sand, and the method comprises the following steps:

[0009] (1) fitting a standard substance containing the component to be measured to obtain a fitting standard sample, and then preparing a fitting standard sample by a melting method;

[0010] (2) Using X-ray fluorescence method to analyze the components of the fitting standard sample, and obtain the working curve of the components to be tested in the drainage sand;

[0011] (3) using X-ray fluorescence to measure the fitting standard sample in step (1), calculating a first difference between the standard value and the measured value, and adjusting the working curve in step (2) according to the first difference; then using X-ray fluorescence to measure the fitting standard sample in step (1), calculating a second difference between the standard value and the measured value, and verifying the reproducibility of the chemical composition of the fitting standard sample detected by the working curve in step (2) according to the second difference;

[0012] (4) A drainage sand sample to be tested is prepared by a molten sheet method. Under the working curve of the component to be tested in the drainage sand determined in step (3), an X-ray fluorescence method is used to analyze the composition of the drainage sand sample to be tested, so as to obtain the content of the component to be tested in the drainage sand.

[0013] In the present invention, the working curve of the components to be measured in the drainage sand refers to the corresponding relationship curve between the different contents and strengths of the components to be measured; the multi-component means that the determination method of the present invention is applicable to the determination of multiple components to be measured in the drainage sand.

[0014] The determination method provided by the present invention adopts a combination of fusion sample preparation and X-ray fluorescence melt analysis to perform component analysis on drainage sand, and can obtain the contents of substances such as chromium trioxide, silicon dioxide, iron trioxide, aluminum trioxide and zirconium dioxide in the drainage sand at one time. The determination method improves the accuracy of the determination, and the melt analysis does not involve the problem of improving the particle effect in the pressed tablet analysis, and has high accuracy and good stability.

[0015] As a preferred technical solution of the present invention, the component to be tested in step (1) includes a combination of at least four of chromium oxide, silicon dioxide, iron oxide, aluminum oxide or zirconium dioxide. Typical but non-limiting combinations include: a combination of chromium oxide, silicon dioxide, iron oxide and aluminum oxide, a combination of chromium oxide, silicon dioxide, iron oxide and zirconium dioxide, silicon dioxide, iron oxide, aluminum oxide and zirconium dioxide, chromium oxide, silicon dioxide, aluminum oxide and zirconium dioxide, or a combination of chromium oxide, silicon dioxide, iron oxide, aluminum oxide and zirconium dioxide.

[0016] Preferably, the selection criteria for the standard substance in step (1) is: a standard substance whose concentration of the component to be measured changes in a gradient.

[0017] Preferably, the standard substances include a primary standard substance of chromite, a primary standard substance of silica and zirconium dioxide.

[0018] Preferably, the purity of the zirconium dioxide is ≥99.99%, for example, it may be 99.99%, 99.992%, 99.994%, 99.996% or 99.998%, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0019] Preferably, the content of the component to be measured in the fitting standard sample is greater than the maximum value of the content of the component to be measured in the drainage sand sample.

[0020] In the present invention, the standard substance refers to a certified standard sample containing chromium trioxide, silicon dioxide, iron trioxide, aluminum trioxide and zirconium dioxide and having an accurate value.

[0021] For example, the primary chromite standard material with the standard number of GSB D33001-94, the primary silica standard material with the standard number of YSBC28764-95 and the certified high-purity zirconium dioxide with a purity of 99.99% are selected for fitting, and the calculation of the composition content of the fitting materials is shown in Table 1.

[0022] Table 1

[0023]

[0024]

[0025] As a preferred technical solution of the present invention, the fitting in step (1) includes: performing fitting calculations based on the contents of chromium oxide, silicon dioxide, iron oxide, aluminum oxide and zirconium dioxide in the standard substance to obtain a fitting standard substance with a gradient change in component concentration.

[0026] As a preferred technical solution of the present invention, the sample preparation method of the fitting standard sample and the drainage sand sample to be tested includes: mixing the sample, lithium carbonate and boric acid, and pre-oxidizing after wrapping with quantitative filter paper, and after cooling, successively mixing lithium tetraborate flux and lithium bromide for heating and melting to obtain a glass sample.

[0027] In the present invention, the lithium tetraborate flux is anhydrous lithium tetraborate, which has the functions of lowering the melting point of the sample and improving the uniformity of the sample during melting.

[0028] As a preferred technical feature of the present invention, the mass ratio of the sample to lithium carbonate is 1:6 to 10, for example, it can be 1:6, 1:6.5, 1:7, 1:7.5, 1:8, 1:8.5, 1:9, 1:9.5 or 1:10, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0029] Preferably, the mass ratio of the sample to boric acid is 1:2-6, for example, 1:2, 1:2.5, 1:3, 1:3.5, 1:4, 1:4.5, 1:5, 1:5.5 or 1:6, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0030] It is worth noting that after determining the mass ratio of the sample to lithium carbonate or boric acid, the ratio cannot be changed again during the test process to ensure the accuracy of the test results.

[0031] Preferably, the pre-oxidation temperature is 900-950°C, for example, 900°C, 910°C, 920°C, 930°C, 940°C or 950°C, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0032] Preferably, the endpoint of the pre-oxidation is that the sample is in a beaded shape and the filter paper ash is burned out.

[0033] Preferably, the mass ratio of the sample to the lithium tetraborate flux is 1:22-25, for example, it can be 1:22, 1:22.3, 1:22.6, 1:22.9, 1:23.2, 1:23.5, 1:23.8, 1:24.1, 1:24.4, 1:24.7 or 1:25, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0034] Preferably, the mass ratio of the sample to lithium bromide is 1:0.04-0.044, for example, 1:0.04, 1:0.041, 1:0.042, 1:0.043 or 1:0.044, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0035] Preferably, the heating and melting temperature is 1050-1100°C, for example, 1050°C, 1060°C, 1070°C, 1080°C, 1090°C or 1100°C, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0036] Preferably, the device used for heating and melting comprises a platinum-gold crucible.

[0037] As a preferred technical solution of the present invention, the correlation coefficient of the working curve in step (2) is 0.9990 to 0.99999, for example, it can be 0.9990, 0.9995, 0.9999, 0.99995 or 0.99999, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0038] As a preferred technical solution of the present invention, the first difference in step (3) is: the difference between the standard value of the content of the component to be measured in the fitting standard sample and the measured value obtained by measuring the fitting standard sample using X-ray fluorescence method.

[0039] Preferably, the method for correcting the working curve in step (2) according to the first difference comprises:

[0040] If the first difference is ≤0.60%, there is no need to adjust the working curve in step (2);

[0041] If the difference is greater than 0.60%, the composition of the fitted standard sample of the component content to be measured is adjusted until the first difference is less than or equal to 0.60%.

[0042] As a preferred technical solution of the present invention, the second difference in step (3) is the difference between the standard value of the content of the component to be measured in the fitting standard sample and the measured value obtained by measuring the fitting standard sample using an X-ray fluorescence method;

[0043] Preferably, the method for correcting the working curve in step (2) according to the second difference comprises:

[0044] If the second difference is ≤0.60%, there is no need to adjust the working curve in step (2);

[0045] If the difference is greater than 0.60%, the composition of the fitted standard sample of the component content to be measured is adjusted until the second difference is less than or equal to 0.60%.

[0046] As a preferred technical solution of the present invention, before the step (3) of measuring the fitting standard sample in step (1), the step further includes: preparing the fitting standard sample in step (1) by the melting plate method.

[0047] As a preferred technical solution of the present invention, the sampling method of the drainage sand sample to be tested in step (4) is: the drainage sand sample is crushed and ground in sequence, and then loaded to obtain the drainage sand sample to be tested.

[0048] Preferably, the particle size of the crushed drainage sand sample is ≤0.125 mm, for example, it can be 0.125 mm, 0.124 mm, 0.122 mm, 0.12 mm, 0.118 mm, 0.116 mm, 0.114 mm, 0.112 mm or 0.1 mm, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0049] Preferably, the grinding time is 110 to 130 seconds, for example, 110 seconds, 114 seconds, 118 seconds, 122 seconds, 126 seconds or 130 seconds, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0050] Preferably, the sample container comprises a ground-mouth bottle or a sample bag containing a protective film.

[0051] The numerical range described in the present invention not only includes the point values ​​listed above, but also includes any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0052] Compared with the prior art, the present invention has the following beneficial effects:

[0053] (1) The determination method provided by the present invention adopts a method combining fusion sample preparation and X-ray fluorescence melt analysis to analyze the composition of drainage sand, and can obtain the contents of chromium trioxide, silicon dioxide, iron trioxide, aluminum trioxide and zirconium dioxide in the drainage sand at one time;

[0054] (2) The melt analysis in the determination method provided by the present invention does not involve improving the particle effect problem in the pressed tablet analysis, thereby improving the accuracy. BRIEF DESCRIPTION OF THE DRAWINGS

[0055] Figure 1 A flow chart of a method for determining the content of multiple components in drainage sand provided by the present invention;

[0056] Figure 2 This is a working curve of the chromium trioxide content in the drainage sand obtained by testing in Example 1 of the present invention;

[0057] Figure 3 This is the working curve of the silicon dioxide content in the drainage sand obtained by testing in Example 2 of the present invention;

[0058] Figure 4The working curve of the ferric oxide content in the drainage sand obtained by testing in Example 3 of the present invention;

[0059] Figure 5 This is the working curve of the aluminum oxide content in the drainage sand tested in Example 4 of the present invention.

[0060] Figure 6 This is the working curve of the zirconium dioxide content in the drainage sand tested in Example 5 of the present invention. DETAILED DESCRIPTION

[0061] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0062] The present invention provides a method for determining the content of multiple components in drainage sand, such as Figure 1 As shown, the determination method comprises the following steps:

[0063] (1) fitting a standard substance containing the component to be measured to obtain a fitting standard sample, and then preparing a fitting standard sample by a melting method;

[0064] The selection criteria of the standard substance are: the standard substance whose concentration of the component to be tested changes in a gradient; the content of the component to be tested in the fitting standard sample> the maximum value of the content of the component to be tested in the drainage sand sample;

[0065] (2) Using X-ray fluorescence method to analyze the components of the fitting standard sample, and obtain the working curve of the components to be tested in the drainage sand;

[0066] The correlation coefficient of the working curve is > 0.9999;

[0067] (3) using X-ray fluorescence to measure the fitting standard sample in step (1), calculating a first difference between the standard value and the measured value, and adjusting the working curve in step (2) according to the first difference; then using X-ray fluorescence to measure the fitting standard sample in step (1), calculating a second difference between the standard value and the measured value, and verifying the reproducibility of the chemical composition of the fitting standard sample detected by the working curve in step (2) according to the second difference;

[0068] (4) A drainage sand sample to be tested is prepared by a molten sheet method. Under the working curve of the component to be tested in the drainage sand determined in step (3), an X-ray fluorescence method is used to analyze the composition of the drainage sand sample to be tested, so as to obtain the content of the component to be tested in the drainage sand.

[0069] The equipment and samples used in the following embodiments and comparative examples of the present invention are as follows:

[0070] 1) Equipment

[0071] Name: electronic balance, manufacturer: Sartorius Scientific Instruments (Beijing) Co., Ltd., equipment model: BSA124S;

[0072] Name: Fully automatic multi-head melting machine, Manufacturer: Shanghai Yusuo Industrial Co., Ltd., Model: DY511

[0073] Name: X-ray fluorescence spectrometer, manufacturer: Bruker, Germany, equipment model: S8-TIGERⅡ;

[0074] 2) Samples

[0075] The standard material package used in the present invention includes: chromite of GSBD 33001-94, GSBD 33001.1-94, GSBD 33001.2-94, GBW07821; silica of YSBC 28764; zirconium dioxide 99.99% of NCS1748.

[0076] Example 1

[0077] This embodiment provides a method for determining the content of multiple components in drainage sand. The component to be determined in this embodiment is chromium trioxide. The determination method comprises the following steps:

[0078] (1) fitting the standard materials chromite, silica, and zirconium dioxide according to the chromium trioxide content in the standard materials, and obtaining fitting standard samples with chromium trioxide contents of 16.40%, 21.31%, 14.76%, 25.42%, 38.8%, 7.76%, 32.20%, 50.95%, and 54.91%, respectively, and then preparing fitting standard samples by the melting method;

[0079] (2) The chromium trioxide composition of the fitting standard sample was analyzed by X-ray fluorescence spectrometer, and the working curve of chromium trioxide in drainage sand was obtained: y = 0.8900x-0.4176, R 2 =0.999670 (e.g. Figure 2 shown);

[0080] (3) using an X-ray fluorescence spectrometer to measure again the fitting standard samples with chromium trioxide contents of 16.40%, 21.31%, 14.76%, 25.42%, 38.8%, 7.76%, 32.20%, 50.95%, and 54.91%, respectively, and calculating the first difference between the standard value and the measured value. If the first difference is ≤0.60%, there is no need to adjust the working curve in step (2); if the first difference is greater than 0.60%, the composition of the fitting standard sample of chromium trioxide content is adjusted until the first difference is ≤0.60%;

[0081] Then, a new set of the fitting standard samples described in step (1) is selected for melting, and the composition is determined by X-ray fluorescence method, and the second difference between the standard and the measured value is calculated. If the second difference is ≤0.60%, there is no need to adjust the working curve described in step (2); if the second difference is greater than 0.60%, the composition of the fitting standard sample of chromium trioxide content is adjusted until the second difference is ≤0.60%;

[0082] (4) preparing a drainage sand sample to be tested by a fused sheet method, and performing component analysis on the drainage sand sample to be tested by an X-ray fluorescence method under the working curve of the component to be tested in the drainage sand determined in step (3) to obtain the content of the component to be tested in the drainage sand;

[0083] The sampling method of the drainage sand sample to be tested is: the drainage sand sample is crushed to a particle size of ≤0.125 mm and ground for 120 seconds, and then loaded to obtain the drainage sand sample to be tested;

[0084] The sample preparation method of the fitting standard sample and the drainage sand sample to be tested in this embodiment includes: after mixing the sample with lithium carbonate and boric acid, wrapping it with quantitative filter paper, placing it in a graphite crucible, pre-oxidizing it in a muffle furnace at 920°C for 1h, cooling it, placing it in a platinum gold crucible with lithium tetraborate flux, adding lithium bromide, heating and melting it at 1090°C, and making a glass sample. The mass ratio of the sample to lithium carbonate is 1:8, the mass ratio of the sample to boric acid is 1:4, the mass ratio of the sample to anhydrous lithium tetraborate flux is 1:24, and the mass ratio of the sample to lithium bromide is 1:0.042;

[0085] In the process of testing using an X-ray fluorescence spectrometer in this embodiment, the specific test conditions are: the melting conditions are: melting for 20 minutes, shaking for 8 minutes, standing for 1 minute, pouring for 30 seconds, and cooling for 2 minutes. The test conditions are: spectrometer mode: vacuum, collimator mask corresponding to the sample diameter: 28 mm, mode / time: measurement time (fixed), and the rest of the settings are default settings.

[0086] The content of chromium trioxide in the drainage sand tested in step (4) of this embodiment is 54.75%, and the actual content is 54.91%. This shows that the error between the measured value and the standard value of the determination method provided in this embodiment is less than 0.90%, thereby indicating that the determination method of the present invention is feasible.

[0087] Example 2

[0088] This embodiment provides a method for determining the content of multiple components in drainage sand. The component to be determined in this embodiment is silicon dioxide. The only difference between the determination method and embodiment 1 is that:

[0089] In this embodiment, step (1) is adjusted as follows: fitting the standard substances chromite, silica, and zirconium dioxide according to the silica content in the standard substances to obtain fitting standard samples with silica contents of 31.05%, 23.75%, 49.30%, 34.77%, 9.63%, 63.62%, 16.54%, 3.56%, and 1.045%, respectively, and then the fitting standard sample is prepared by the fusion method.

[0090] The working curve of silica in drainage sand obtained by using the above fitting standard sample is: y = 2.405x-0.0872, R 2 =0.999927 (e.g. Figure 3 shown);

[0091] In step (4) of this embodiment, the content of silicon dioxide in the drainage sand is tested to be 16.27%, and the actual content is 16.54%. This shows that the error between the measured value and the standard value of the determination method provided in this embodiment is less than 0.57%, thereby indicating that the determination method of the present invention is feasible.

[0092] Example 3

[0093] This embodiment provides a method for determining the content of multiple components in drainage sand. The component to be determined in this embodiment is ferric oxide. The difference between the determination method and embodiment 1 is that:

[0094] In this embodiment, step (1) is adjusted as follows: fitting the standard substances chromite, silica, and zirconium dioxide according to the iron oxide content in the standard substance to obtain fitting standard samples with iron oxide contents of 6.91%, 8.91%, 6.30%, 9.82%, 25.13%, 5.27%, 20.89%, 17.96%, and 8.763%, respectively, and then preparing fitting standard samples by the melting method;

[0095] The working curve of ferric oxide in drainage sand obtained by using the above fitting standard sample is: y = 0.4569x-3.033, R 2 =0.999924 (e.g. Figure 4 shown);

[0096] In step (4) of this embodiment, the content of ferric oxide in the drainage sand is tested to be 9.68%, and the actual content is 9.82%. This shows that the error between the measured value and the standard value of the determination method provided in this embodiment is less than 0.195%, thereby indicating that the determination method of the present invention is feasible.

[0097] Example 4

[0098] This embodiment provides a method for determining the content of multiple components in drainage sand. The component to be determined in this embodiment is aluminum oxide. The difference between the determination method and embodiment 1 is that:

[0099] In this embodiment, step (1) is adjusted as follows: fitting the standard substances chromite, silica, and zirconium dioxide according to the aluminum oxide content in the standard substance to obtain fitting standard samples with silicon dioxide contents of 5.25%, 6.40%, 5.27%, 8.36%, 12.76%, 4.13%, 10.81%, 13.12%, and 10.004%, respectively, and then the fitting standard sample is prepared by the melting method;

[0100] The working curve of aluminum oxide in drainage sand obtained by using the above fitting standard sample is: y = 1.284x-0.8916, R 2 =0.999006 (e.g. Figure 5 shown);

[0101] In step (4) of this embodiment, the content of aluminum oxide in the drainage sand is tested to be 3.8%, and the actual content is 4.13%. This shows that the error between the measured value and the standard value of the determination method provided in this embodiment is less than 0.36%, thereby indicating that the determination method of the present invention is feasible.

[0102] Example 5

[0103] This embodiment provides a method for determining the content of multiple components in drainage sand. The component to be determined in this embodiment is zirconium dioxide. The difference between the determination method and embodiment 1 is that:

[0104] In this embodiment, step (1) is adjusted as follows: fitting the standard substances chromite, silica, and zirconium dioxide according to the zirconium dioxide content in the standard substances to obtain fitting standard samples with silicon dioxide contents of 25.00%, 20.00%, 10.00%, 2.00%, 15.00%, 8.00%, and 5.00%, respectively, and then preparing fitting standard samples by the melting method;

[0105] The working curve of zirconium dioxide in drainage sand obtained by using the above fitting standard sample is: y = 0.09448x-3.049, R 2 =0.999751(such as Figure 6 shown);

[0106] In step (4) of this embodiment, the content of zirconium dioxide in the drainage sand is tested to be 4.70%, and the actual content is 5.00%. This shows that the error between the measured value and the standard value of the determination method provided in this embodiment is less than 0.48%, thereby indicating that the determination method of the present invention is feasible.

[0107] Comparative Example 1

[0108] This comparative example provides a method for determining the content of multiple components in drainage sand. The component to be determined in this comparative example is chromium trioxide, and the determination method includes:

[0109] The drainage sand samples to be tested were pressed into tablets using a sample press, and then semi-quantitatively analyzed using an X-ray fluorescence spectrometer.

[0110] The content of chromium trioxide in the drainage sand tested in the above method is 55.07%, and the actual content is 54.91%.

[0111] Although the determination method provided in this comparative example can also achieve the determination of the chromium trioxide content in the drainage sand, its analysis time is long and there are disadvantages such as the influence of particle effect.

[0112] In summary, the present invention adopts a method combining fusion sampling and X-ray fluorescence melt analysis to perform component analysis on drainage sand, and can obtain the contents of substances such as chromium trioxide, silicon dioxide, iron trioxide, aluminum trioxide and zirconium dioxide in the drainage sand at one time. The determination method improves the detection efficiency, and the melt analysis does not involve the problem of improving the particle effect in the pressed tablet analysis, and has a high accuracy.

[0113] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for determining the content of multiple components in drainage sand, characterized in that: The determination method comprises the following steps: (1) fitting a standard substance containing the component to be measured to obtain a fitting standard sample, and then preparing a fitting standard sample by a melting method; (2) Using X-ray fluorescence method to analyze the components of the fitting standard sample, and obtain the working curve of the components to be tested in the drainage sand; (3) using X-ray fluorescence to measure the fitting standard sample in step (1), calculating a first difference between the standard value and the measured value, and adjusting the working curve in step (2) according to the first difference; then using X-ray fluorescence to measure the fitting standard sample in step (1), calculating a second difference between the standard value and the measured value, and verifying the reproducibility of the chemical composition of the fitting standard sample detected by the working curve in step (2) according to the second difference; (4) A drainage sand sample to be tested is prepared by a molten sheet method. Under the working curve of the component to be tested in the drainage sand determined in step (3), an X-ray fluorescence method is used to analyze the composition of the drainage sand sample to be tested, so as to obtain the content of the component to be tested in the drainage sand.

2. The measuring method according to claim 1, characterized in that The component to be tested in step (1) comprises a combination of at least four of chromium oxide, silicon dioxide, iron oxide, aluminum oxide or zirconium dioxide; Preferably, the selection criteria of the standard substance in step (1) are: standard substance whose concentration of the component to be measured changes in a gradient; Preferably, the standard substances include a primary standard substance of chromite, a primary standard substance of silica and zirconium dioxide; Preferably, the purity of the zirconium dioxide is ≥99.99%; Preferably, the content of the component to be measured in the fitting standard sample is greater than the maximum value of the content of the component to be measured in the drainage sand sample.

3. The measuring method according to claim 1 or 2, characterized in that The fitting in step (1) includes: performing fitting calculations based on the contents of chromium oxide, silicon dioxide, iron oxide, aluminum oxide and zirconium dioxide in the standard substance to obtain a fitting standard substance with a gradient change in component concentration.

4. The assay method according to any one of claims 1 to 3, characterized in that The sample preparation method of the fitting standard sample and the drainage sand sample to be tested comprises: mixing the sample, lithium carbonate and boric acid, wrapping with quantitative filter paper and then pre-oxidizing, and after cooling, sequentially mixing lithium tetraborate flux and lithium bromide and heating and melting to obtain a glass sample.

5. The measuring method according to claim 4, characterized in that The mass ratio of the sample to lithium carbonate is 1:6-10; Preferably, the mass ratio of the sample to boric acid is 1:2-6; Preferably, the pre-oxidation temperature is 900-950°C; Preferably, the endpoint of the pre-oxidation is: the sample is in bead form and the filter paper ash is burned out; Preferably, the mass ratio of the sample to the lithium tetraborate flux is 1:22-25; Preferably, the mass ratio of the sample to lithium bromide is 1:0.04-0.044; Preferably, the heating and melting temperature is 1050-1100°C; Preferably, the device used for heating and melting comprises a platinum-gold crucible.

6. The assay method according to any one of claims 1 to 5, characterized in that The correlation coefficient of the working curve in step (2) is 0.9990 to 0.99999.

7. The assay method according to any one of claims 1 to 6, characterized in that Step (3) the first difference is: the difference between the standard value of the content of the component to be measured in the fitting standard sample and the measured value obtained by measuring the fitting standard sample using the X-ray fluorescence method; Preferably, the method for correcting the working curve in step (2) according to the first difference comprises: If the first difference is ≤0.60%, there is no need to adjust the working curve in step (2); If the difference is greater than 0.60%, the composition of the fitted standard sample of the component content to be measured is adjusted until the first difference is less than or equal to 0.60%.

8. The assay method according to any one of claims 1 to 7, characterized in that Step (3) the second difference is the difference between the standard value of the content of the component to be measured in the fitting standard sample and the measured value obtained by measuring the fitting standard sample using X-ray fluorescence method; Preferably, the method for correcting the working curve in step (2) according to the second difference comprises: If the second difference is ≤0.60%, there is no need to adjust the working curve in step (2); If the difference is greater than 0.60%, the composition of the fitted standard sample of the component content to be measured is adjusted until the second difference is less than or equal to 0.60%.

9. The determination method according to any one of claims 1 to 8, characterized in that Before the determination of the fitting standard sample in step (1) in step (3), the method further includes: re-preparing the fitting standard sample in step (1) by the melting plate method.

10. The determination method according to any one of claims 1 to 9, characterized in that: The sampling method of the drainage sand sample to be tested in step (4) is: crushing and grinding the drainage sand sample in sequence, and then loading the sample to obtain the drainage sand sample to be tested; Preferably, the particle size of the crushed drainage sand sample is ≤0.125 mm; Preferably, the grinding time is 110 to 130 seconds; Preferably, the sample container comprises a ground-mouth bottle or a sample bag containing a protective film.

Citation Information

Cited By

  • Calculation method and evaluation method for secondary oxidation capacity of stuffing sand to molten steel

    CN120869859A